2023
DOI: 10.3390/insects14040378
|View full text |Cite
|
Sign up to set email alerts
|

Climate and Environmental Changes and Their Potential Effects on the Dynamics of Chagas Disease: Hybridization in Rhodniini (Hemiptera, Triatominae)

Abstract: Chagas disease affects about eight million people. In view of the issues related to the influence of anthropogenic changes in the dynamics of the distribution and reproductive interaction of triatomines, we performed experimental crosses between species of the Rhodniini tribe in order to evaluate interspecific reproductive interactions and hybrid production capacity. Reciprocal crossing experiments were conducted among Rhodnius brethesi × R. pictipes, R. colombiensis × R. ecuadoriensis, R. neivai × R. prolixus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Recently, Ravazi et al 51 evaluated the hybridization capacity of species from the Rhodniini tribe that live in sympatry and parapatry in the face of anthropogenic changes (environmental and climate changes). The authors observed that hybrids were produced in at least one direction of all crosses performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ravazi et al 51 evaluated the hybridization capacity of species from the Rhodniini tribe that live in sympatry and parapatry in the face of anthropogenic changes (environmental and climate changes). The authors observed that hybrids were produced in at least one direction of all crosses performed.…”
Section: Discussionmentioning
confidence: 99%